Information Hiding Application Using Digital Images Secured With Rijndael and Caesar Cipher Encryption - Jonathan Surya; Abdul Ghofir (IT for Society, 2019)
Steganography is a way thtt conceals or embeds important data in form of text file into an image which possible to reduce and erase the existence of the data. A modern steganography can help millions of people to protect their data from potential threats or other individuals using computer programs and algorithm. This paper proposed an implementation of steganography Rijndael and Caesar schemes . This application will let the user embed the important data/information to an image and encrypt it.